Implementation of Station-To-Station (STS) protocol using Elliptic Curve Digital Signature Al Algorithm / Muhammad Faris Fakhri Rozi, Alya Syuhada Ismail and Emylia Suhaimi - Rozi, Muhammad Faris Fakhri; Ismail, Alya Syuhada; Suhaimi, Emylia (2018)
Diffie-Hellman key exchange is a protocol to exchange key between two parties. Unfortunately, the Diffie-Hellman protocol is not save from intruder such as Man-In-The -Middle (MITM) attack because it allows two parties changing the secret key to an unsecured communication without any meeting due to Diffie-Hellman key exchange does not have an authentication element. Elliptic Curve Digital Signature Algorithms (ECDSA) is implemented in Station-To¬ Station protocol in order to give an improvement in the secret key exchange between two parties. This protocol will provide an element of authentication element and data integrity in the system. This project was developed into a Graphical User Interface (GUI) using MAPLE software to show how the system works. It was believed that this implementation has increased the level of secrecy in the sharing session using the method applied. Throughout this study another improvement is recommended to be applied in order to provide data integrity into the system as current scope of the study only focus on the element of authentication.